Contrasting contributions of anhedonia to obsessive-compulsive, hoarding, and post-traumatic stress disorders. (February 2019) - Pushkarskaya, Helen; Sobowale, Kunmi; Henick, Daniel; Tolin, David F.; Anticevic, Alan; Pearlson, Godfrey D.; Levy, Ifat; Harpaz-Rotem, Ilan; Pittenger, Christopher
Abstract: Anhedonia is a transdiagnostic construct that can occur independent of other symptoms of depression; its role in neuropsychiatric disorders that are not primarily affective, such as obsessive compulsive disorder (OCD), hoarding disorder (HD), and post-traumatic stress disorder (PTSD) has received limited attention. This paper addresses this gap. First, the data revealed a positive contribution of anhedonia, beyond the effects of general depression, to symptom severity in OCD but not in HD or PTSD. Second, anhedonia was operationalized as a reduced sensitivity to rewards, which allowed employing the value based decision making framework to investigate effects of anhedonia on reward-related behavioral outcomes, such as increased risk aversion and increased difficulty of making value-based choices. Both self-report and behavior-based measures were used to characterize individual risk aversion: risk perception and risk-taking propensities (measured using the Domain Specific Risk Taking scale) and risk attitudes evaluated using a gambling task. Data revealed the positive theoretically predicted correlation between anhedonia and risk perception in OCD; effects on self-reported risk taking and behavior-based risk aversion were non-significant. The same relations were weaker in HD and absent in PTSD. Response time during a gambling task, an index of difficulty of making value-based choices, significantly correlated with anhedonia in individuals with OCD and individuals with HD, even after controlling for general depression, but not in individuals with PTSD. The results suggest a unique contribution of one aspect of anhedonia in obsessive-compulsive disorder and confirm the importance of investigating the role of anhedonia transdiagnostically beyond affective and psychotic disorders.